Contracting Out, Grievance Procedure and Union Liability - J., Locke (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1960)
SummaryThough the preferential wiring clause did not apply to an independant contractor, the union could not put him off the job, the matter beeing one which should have been dealt with accordingly under the grievance procedure clause. The union a legal entity, by the use of illegal means, caused damage to the respondent and is liable in damages for its wrongful acts, through the act of the union was not done in connection with a trade dispute.